Analisis Uji Permeabilitas Total Sumur Berdasarkan Well Completion Test Pada Sumur RL-25 Lapangan Panas Bumi Area CLX - Rial Dwi Martasari; Sayu Mulhasyim; Dwi Arifiyanto (Jurnal Migasian, 2023)
Well completion test (Well Completion test) in general is a test to determine the characteristics and potential production wells as well as provide information about the truth of targeting achieved in drilling include permeable zone data. Activities include exploratory well completion test the depth, temperature and pressure measurement wells, water loss test (test of water lost), gross permeability test (total permeability test). From the analysis of pressure and temperature ramp then gained the feed zone wells MKU RL-25 1660-2000. Water loss test aims to determine the permeable area by injecting cold water into the well. Based on data from the test water loss KTE position is placed on the well depth of 2000 MKU to RL-25 with such tools will be submerged in the water column. Injectivity is a relationship between the flow rate of water injected into the well with the measured pressure in the permeable area. Injectivity (i) an average of 802.681 lpm/Ksc and specific capacity (Ks) averaging 5.029 lpm/meter for wells RL-25. The well RL-25 has a slope (m) of 12 Ksc with pressure at 1 hour (P1 hour) amounted to 45.55 Ksc and initial pressure (Pi) of 32 Ksc with the assumption that the viscosity (μ) of 2.13x10-4 Pa.s and transmissivity ( kh) of 1.753179 darcy meter with skin factor (s) of -0.176.Maka of the data injectivity test get 35 Kg/s that can be estimated at 126 tons/hour and by Spesific Steam Comsumsion to generate electric power of 1 MW at 8 ton/h/MW it can result amounted to 15.75 MW.